Impact of Post‐Lithography Polymer Residue on the Electrical Characteristics of MoS2 and WSe2 Field Effect Transistors. Issue 3 (3rd December 2018) - Liang, Jierui; Xu, Ke; Toncini, Blaec; Bersch, Brian; Jariwala, Bhakti; Lin, Yu‐Chuan; Robinson, Joshua; Fullerton‐Shirey, Susan K.
Abstract: The residue of common photo‐ and electron‐beam resists, such as poly(methyl methacrylate) (PMMA), is often present on the surface of 2D crystals after device fabrication. The residue degrades device properties by decreasing carrier mobility and creating unwanted doping. Here, MoS2 and WSe2 field effect transistors (FETs) with residue are cleaned by contact mode atomic force microscopy (AFM) and the impact of the residue on: 1) the intrinsic electrical properties, and 2) the effectiveness of electric double layer (EDL) gating are measured. After cleaning, AFM measurements confirm that the surface roughness decreases to its intrinsic state (i.e., ≈0.23 nm for exfoliated MoS2 and WSe2 ) and Raman spectroscopy shows that the characteristic peak intensities (E2g and A1g ) increase. PMMA residue causes p‐type doping corresponding to a charge density of ≈7 × 10 11 cm −2 on back‐gated MoS2 and WSe2 FETs. For FETs gated with polyethylene oxide (PEO)76 :CsClO4, removing the residue increases the charge density by 4.5 × 10 12 cm −2, and the maximum drain current by 247% (statistically significant, p < 0.05). Removing the residue likely allows the ions to be positioned closer to the channel surface, which is essential for achieving the best possible electrostatic gate control in ion‐gated devices. Abstract : The impact of post‐lithography polymer residue on MoS2 and WSe2 is investigated on back‐gated and ionic‐gated field effect transistors. The removal of the residue is achieved by contact‐mode AFM without degrading the electronic properties, which increases charge density for back‐gated devices and enhances the gate coupling in ionic‐gated devices by increasing the proximity of ions to the 2D surface.